Gastric Siderosis and Ulceration from Intravenous Iron Supplementation Manifesting as Chronic Upper Gastrointestinal Bleeding: A Case Report and Review of the Literature - Donald Ewing; Ava Brozovich; Ethan Burns; Gonzalo Acosta; Courtney Hatcher; Pragnesh Patel; Rose Anton; Bincy Abraham; Leena Samuel (Case Reports in Gastrointestinal Medicine)
Iron deficiency is the most common etiology of anemia worldwide and is often managed with varying methods of iron supplementation. Although rare, oral iron supplementation can perpetuate iron deficiency anemia by causing gastric ulceration and upper gastrointestinal bleeding in high-risk populations. However, this complication has not been previously described with intravenous iron supplementation. We present a case of a 63-year-old male with severe iron deficiency anemia on biweekly intravenous iron infusions and weekly packed red blood cell transfusions who presented with melena over several months. Upper endoscopy demonstrated a clean-based gastric body ulcer and nonbleeding gastric varices. Histology of the gastric ulcer was suggestive of iron-induced gastric mucosal injury. This case demonstrates that frequent utilization of intravenous iron and packed red blood cell transfusions may predispose certain patients to the development of iron-induced gastritis and ulceration.